Information Sharing and Incentives in Organizations - Jean-Etienne de Bettignies; Jan Zabojnik (Queen's University, Department of Economics, 2013)
We examine optimal information flows between a manager and a worker who is in charge of evaluating a parameter of interest, e.g. the value of a project. The manager may possesses information about the parameter, and, if informed, may divulge her information to the worker. We show that information sharing may weaken the worker's incentives and that, consequently, the manager may find it optimal to conceal her information from the worker. Moreover, the manager faces a time-inconsistency problem, which leads her to conceal her information more often than she would if she could commit to an information sharing policy. We build on these results to address issues related to authority in organizations.
Keywords: D21; D82; L23; 330; Information non-disclosure; expert evaluation; agency costs; authority